Sex Pheromone of the Introduced Pine Sawfly, Diprion similis, Revisited to Define a Useful Monitoring Lure: Deviating Chiral Composition and Behavioural Responses Compared to Earlier Reports - Olle Anderbrant; D. Barry Lyons; Joakim Bång; Erik Hedenström; Hans-Erik Högberg (Insects, 2021)
Extracts of Diprion similis females contained about 15 ng of the sex pheromone precursor 3,7-dimethylpentadecan-2-ol per female. After derivatisation with (S)-2-acetoxypropanoyl chloride, we found that the major stereoisomer in the extract was (2S,3R,7R)-3,7-dimethylpentadecan-2-ol. Small amounts of other stereoisomers of 3,7-dimethylpentadecan-2-ol were also identified in the extract, namely 1% of (2R,3S,7S), 0.3% (2R,3R,7R) and 0.4% of (2R,3R,7S). An unknown fifth substance showed a very similar spectrum to 3,7-dimethylpentadecan-2-ol, both in SIM and full scan mode. None of the earlier suggested behavioural synergistic isomers ((2S,3S,7S), (2S,3S,7R) and (2S,3R,7S)) were detected in the extracts. In field tests in Ontario, Canada, the earlier identified main pheromone component, viz. the propanoate of (2S,3R,7R)-3,7-dimethylpentadecan-2-ol, was tested alone and in combination with other stereoisomers, earlier reported to be synergistic. No synergistic effects were detected and the threo four-isomer blend was as attractive as the pure main compound. Thus, one of the few examples of a diprionid sawfly using more than one substance in its sex pheromone could not be confirmed. The results also suggest that monitoring programs can use the more easily synthesized threo-blend without losing efficiency. Furthermore, the study suggests that other diprionid pheromones may benefit from a reinvestigation, to clarify possible synergistic effects of stereoisomers.